On the identity of two species of Proctophyllodidae (Acari: Astigmata: Analgoidea) described by Herbert F. Berla in Brazil, with a description of Lamellodectes gen. nov and a new species - Hernandes, Fabio A. [UNESP]; Valim, Michel P. (Magnolia Press, 2014)
Two proctophyllodid species described by Herbert F. Berla were studied, re-described and their generic status was re-evaluated. A new genus, Lamellodectes gen. nov. (Proctophyllodidae: Pterodectinae), is erected to accommodate Pterodectes ocelatus Berla, 1960 from the White-collared Foliage-gleaner, Anabazenops fuscus (Vieillot) (Furnariidae), and a new species, L. distinctus sp. nov., from the Double-collared seedeater, Sporophila caerulescens (Emberizidae). Proctophyllodes minor Berla, 1959a is herein transferred to the genus Platyacarus Kudon, 1982a (Proctophyllodinae) and given a valid name Platyacarus minor (Berla) comb. nov. Updated keys to subfamilies and genera of the family Proctophyllodidae are presented. In addition, the known biogeographical distribution for each genus is summarized.
Keywords: Feather mites; Astigmata; Pterodectinae; new genus; Platyacarus; Lamellodectes